Gastrointestinal endoscopy and work-related injuries: an international survey - Bessone, Veronica; Adamsen, Sven (Endoscopy International Open, 2022)
Background and study aims Recently, the awareness of work-related musculoskeletal injuries (MSIs) among gastrointestinal endoscopists has increased because of their effect on the private and work life of clinicians as well as on the health care system. The high injury incidence (reported to range from 37 % to 89 %) has been correlated with the intensive muscular demand required during a procedure.Patients and methods An online survey with 32 questions was conducted globally. Clinically active endoscopists (doctors and nurses) participated anonymously and voluntarily. The questionnaire included questions about endoscopist anthropometrics, experience of MSI, treatment, and preventive measures such as ergonomic training. Descriptive statistics were used to analyse the data.Results Of 204 clinicians (78 % males; 81 % > 35 years of age), 107 (53 %) stated to have experienced a work-related MSI. The most frequent locations were in the neck (n = 49), shoulder and thumb (n = 39, both). Female clinicians resulted to be significantly more prone to develop MSI. In addition, endoscopists who performed more than 15 hours of endoscopy or more than 15 procedures per week reported a significantly higher rate of MSI.Conclusions The high frequency of MSIs among gastrointestinal endoscopists highlights the importance of implementing ergonomic training. Including simple precautions before and during endoscopy may reduce the risk of developing an injury.